FACTORS CAUSING EARLY OSTEOPOROSIS IN PERIMENOPAUSAL WOMEN - Qamar, Muhammad Aslam; Durrani, Mehwish; Nazli, Rubina; Abubakar, Muhammad; Shafiq, Muhammad (Pakistan Journal of Physiology, 2015)
Osteoporosis is a major problem particularly in women. The objective of this study was to evaluate effects of urbanization, high socio-economic status, and decreased ambulation for early osteoporosis in perimenopausal women. Methods: This was a descriptive cross-sectional study carried out in Postgraduate Medical Institute, Hayatabad Medical Complex, Peshawar from June to Aug 2012. Our study population was peri-menopausal women assessed radiographically for osteoporosis. The levels of carboxy-terminal collagen cross-links (CTX-I) as a marker of bone degradation were determined. These women were randomly selected and screened for osteoporosis. In addition, haemoglobin, erythrocyte sedimentation rate (ESR), serum calcium and serum alkaline phosphatase levels were determined. Radiographic grading of osteoporosis was done according to Singh index as I to VI. Results: High levels of CTX-I were observed in perimenopausal women who were radiographically diagnosed as osteoporotic patients. High socio-economic class also is predisposed to steoporosis. Decreased ambulation was significantly associated with increased levels of CTX-I. Conclusion: Both decreased ambulation and high socioeconomic class had significant association with increased levels of serum CTX-I.